New Chicago Views on Inflation Control: The Neo-Fisherian Approach and the Fiscal Theory of the Price Level - Peter Spahn (Credit and Capital Markets – Kredit und Kapital, 2019)
Whereas in former times, the 'Chicago View' in monetary policy stood for the Quantity Theory and money supply control, it is now the centre of unconventional approaches in macro theory. The Neo-Fisherian proposal suggests, in the case of low inflation and nominal interest rates pegged to the zero-lower bound, to increase policy rates immediately to the long-run equilibrium value that corresponds to the 'natural' real interest rate and the inflation target. The Fiscal Theory of the Price Level believes that goods prices jump to a level that validates the long-run sustainability condition of government debt even if central banks abstain from monetising. Both views are criticized for analytical and empirical reasons. – – Während in früheren Zeiten die 'Chicago-Sicht' in der Geldpolitik für die Quantitätstheorie und das Konzept der Geldmengensteuerung stand, werden heute damit unkonventionelle Positionen in der makroökonomischen Theorie assoziiert. Der neue Fisher-Ansatz empfiehlt, im Fall niedriger Inflation und einer Beschränkung durch die Null-Zins-Grenze die Zentralbankzinsen direkt auf das Niveau anzuheben, dass durch den 'natürlichen' Realzins und die Zielinflationsrate bestimmt ist. Die Fiskalische Theorie der Preise behauptet, dass das Güterpreisniveau auf einen Wert springt, der die langfristige reale Tragfähigkeit der Staatsschulden sichert, selbst wenn die Notenbank keine Monetisierung betreibt. Beide Positionen können empirisch nicht überzeugen und werden einer analytischen Kritik unterzogen.
Keywords: E52; E58; 330; unconventional interest rate policy; inflation expectations; government budget constraint